OPERATIONAL SECURITY METHODS AND MEANS OF SUPPLY - Khidirova Dildora Zayniddinovna (Bright Mind Publishing, 2025)
Human safety comes first. It is known that safety is the main core of the safety of life activities and is the state of human activity. In this case, people try to eliminate the risks that arise with a certain probability. But in all cases, it is not possible to eliminate risks. For example, in the event of a fire hazard - if it is possible to extinguish the fire in the initial phase, the possibilities of extinguishing it in the next phase are limited, or the indicators used in some technological processes: temperature, pressure indicators suddenly change.
Keywords: Activity, security, process, global, technosphere, homosphere, substance, disheartened.